OP0134 The Rheumatoid Arthritis Susceptibility Gene C5ORF30 Acts as An Immunomodulator in Macrophages. (15th July 2016) - Dorris, E.R.; Creevey, K.; Moran, C.; Muthana, M.; Wilson, A.G.
Abstract : Background: The variant rs26232 in the first intron of C5orf30 has been associated with both risk of developing rheumatoid arthritis (RA) and severity of tissue damage. The gene encodes a protein of 206 amino acids that is highly expressed by RA synovial fibroblasts (RASF) and macrophages. Inhibition of C5orf30 in RASF results in increased cellular invasiveness and migration in vitro, furthermore, inhibition in the collagen-induced arthritis model markedly accentuated joint inflammation and damage, with elevated TNF and IL-1 expression (Muthana et al, 2015). There is no published data on the biological activities of C5orf30 in macrophages. Objectives: To determine the role of C5orf30 in regulating monocyte-derived macrophage biology. Methods: Experiments involving both the monocyte/macrophage cell line (THP1) and primary monocyte-derived macrophages (MDM) were employed. MDMs were isolated from healthy donor PBMCs and cultured on plastic for 8 days with m-CSF. Macrophage purity was confirmed via flow cytometry. Expression of C5orf30 mRNA was assessed by quantitative PCR and protein expression via Western blot. The effects of polarization to M1 and M2a phenotypes and stimulation with TNF and LPS on C5orf30 expression were compared. C5orf30 levels were manipulated using siRNA technology and functional effects on macrophage biology was assessed using cytokine response assays, matrigel transwell invasion assays, quantitative high throughput pathogen phagocytosis assays, gene expression and intracellular signaling. Results: Treatment of macrophages with either TNF or LPS significantly reduced C5orf30 expression compared to untreated cells (TNF 0.51±0.26 p =0.001 and LPS 0.29±0.25 p =0.02). Furthermore, polarization to M2a phenotype trended to increased expression (1.34±0.59 p =0.13) whereas polarization to M1 macrophage phenotype resulted in significantly decreased expression of C5orf30 (0.68±0.13 p= 0.01) compared to untreated cells, indicating an anti-inflammatory effect. Knockdown of C5orf30 significantly reduced the invasive capacity of macrophages (0.54±0.04 p= 0.003); this was intensified upon incubation with either TNF (0.29±0.16 p= 0.02) or LPS (0.34±0.11 p= 0.01). Phagocytosis of labeled yeast particles was increased upon C5orf30 knockdown combined with co-incubation with TNF (1.14 p= 0.02). C5orf30 knockdown also increased activation of the JNK pathway as measured by an increase in phosphoJNK but not total JNK. All knockdown experiments compared to non-targeting (scramble) siRNA control. Conclusions: C5orf30 knockdown enhanced the proinflammatory (M1-like) macrophage phenotypes of pathogen phagocytosis and JNK pathway activation whilst diminishing the tissue-clearing (M2-like) phenotype of macrophage invasion. This data combined with the observation that proinflammatory cytokine stimulation reduced C5orf30 expression indicates an important role for C5orf30 in the immunomodulatory regulation of macrophages and is consistent with our previous findings in RASF that C5orf30 is a negative regulator of tissue damage in rheumatoid arthritis. References: Muthana M, Hawtree S, Wilshaw A, Linehan E, Roberts H, Khetan S, Adeleke G, Wright F, Akil M, Fearon U, Veale D, Ciani B and Wilson AG. C5orf30 is a negative regulator of tissue damage in rheumatoid arthritis. Proceedings of the National Academy of Sciences. 2015; 112(37):11618–23 Acknowledgement: Funding provided by Arthritis Ireland Disclosure of Interest: None declared